Mapeamento dos conflitos ambientais e urbanísticos mediante levantamento de Ações Civis Públicas e Termos Ajustamento de Conduta – estudo de casos da cidade de São Carlos-SP - Santos, Camila Marques dos (2018)
This work presents a methodologic approach to map urbanistic and environmental conflicts using data collection of legal records from 2006 until 2016, in São Carlos region, State of São Paulo. The metodology consists in: literature review, quantitative analysis, characterization and mapping. The literature review sought to group information as possible about the search objects. The data were obtained by analising two types of documented legal instruments (Public Civil Lawsuits and Terms of Conduct Adjustment in Federal and State Justice) that aim to protect public interests. The methodology consisted in collecting data of lawsuits which made possible a quantitative analysis, characterization and mapping forementioned conflicts. For each oft he two legal instruments a database has been created in order to analyze the object of study in terms of duration, nature, defendants and authors. The characterization was carried out by analyzing the obligations for each lawsuit and the creation of subjects and categories, that allowed to identify the main lines of conflict. The mapping was realized by Google Earth Pro software, using geographical location data found in the analyzed documents. These data were subsequently imported into a Geographical Information System, which enabled the creation database statistc analyses of spacial data. The used software was (ESRI ArcGIS, version 10.3). Thus, it was possible to carry out data storage and processing, as well as the documentation of geographic information and mapping of environmental and urban conflicts. Databases allow you to conduct further for future research.